Phenomenology: Meaning and Benefits of Salat Tahajud in Early, Middle, and Late Adult Women - Erico Pratama Nugraha (Universitas Islam Negeri Imam Bonjol Padang, 2023)
In adulthood and old age, every individual is forced to go through a very difficult life transition period, especially for women. There are two ways that can be done to avoid failure in facing demands, namely focusing on dealing with demands (focused problem solving) and focusing on dealing with the emotions behind the demands (focused emotion solving). The success of these two methods can be strengthened by a sense of gratitude that comes from positive experiences when worshiping, especially salat tahajud. Based on the previous explanation, this study aims to obtain a comprehensive picture of the experience of praying tahajud, especially in early, middle, and late adult women. The method used in this study is a qualitative phenomenological research method with a post-positivism paradigm. The number of participants in this experiment was three people. From the results of the thematic analysis, it was found that there were two main themes, namely, (1) worship activities with sub-themes (obligatory prayers, sunnah prayers, sunnah fasting worship, and reading qur'an) and (2) salat tahajud with sub-themes (intensity of tahajud, the reason for the midnight prayer, spiritual experience, the meaning of the midnight prayer, and the benefits of the midnight prayer). The conclusion from the results of this study, salat tahajud, which is used as a routine in worship, can give its own meaning depending on the problems that are being faced by the person who performs salat tahajud. In addition to providing meaning, salat tahajud also provides many benefits for people who carry it out. The perceived benefits can have an impact on psychological, physiological, and behavioral aspects